Analysis of Fertility Preservation by Ovarian Tissue Cryopreservation in Pediatric Children in China - Ruan, Xiangyan; Cheng, Jiaojiao; Du, Juan; Jin, Fengyu; Gu, Muqing; Li, Yanglu; Ju, Rui; Wu, Yurui; Wang, Huanmin; Yang, Wei; Cheng, Haiyan; Li, Long; et al. (Frontiers in Endocrinology, 2022)
Abstract Background: Ovarian tissue cryopreservation (OTC) is the only method of fertility preservation (FP) in prepubertal girls, but the experience remains limited. This study investigates the effectiveness and feasibility of FP of OTC in children facing gonadotoxicity treatment in Chinese first ovarian tissue cryobank. Procedure: OTC and evaluation of 49 children ≤14 years old in the cryobank of Beijing Obstetrics and Gynecology Hospital, Capital Medical University, from July 2017 to May 19, 2022, were analyzed retrospectively. We compared children's general characteristics, follicle numbers, and hormone levels with and without chemotherapy before OTC. Results: The age of 49 children at the time of OTC was 7.55 (1-14) years old. There were 23 cases of hematological non-malignant diseases, 8 cases of hematological malignant diseases, 4 cases of gynecological malignant tumors, 1 case of neurological malignant tumors, 1 case of bladder cancer, and 5 cases of sarcoma, 3 cases of mucopolysaccharide storage disease, 1 case of heterochromatic leukodystrophy, 2 cases of dermatomyositis, 1 case Turner’s syndrome. The median follicular count per 2mm biopsy was 705. Age and AMH were not correlated (r=0.084, P=0.585). Age and follicle count per 2mm biopsy was not correlated (r=-0.128, P=0.403). Log10 (Follicle count per 2mm biopsy) & Log10 (AMH) were not correlated (r=-0.118, P=0.456). Chemotherapy before OTC decreased AMH levels but had no significant effect on the number of follicles per 2mm biopsy. Conclusions: OTC is the only method to preserve the fertility of prepubertal girls, and it is safe and effective. Chemotherapy before OTC is not a contraindication to OTC.